2018
DOI: 10.3390/cells8010006
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium: An Important Source of Structural and Functional Diversity in Drug Discovery

Abstract: The cellular slime mold Dictyostelium discoideum is an excellent model organism for the study of cell and developmental biology because of its simple life cycle and ease of use. Recent findings suggest that Dictyostelium and possibly other genera of cellular slime molds, are potential sources of novel lead compounds for pharmacological and medical research. In this review, we present supporting evidence that cellular slime molds are an untapped source of lead compounds by examining the discovery and functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 114 publications
(215 reference statements)
3
27
0
Order By: Relevance
“…On the other hand, Pf-2 was found to lack any substantial cytotoxicity.Pf-1 and AB0022A exhibited the constraint of the tested cell lines (K562, HeLa and 3T3-L1), which indicates that a free phenolic group connected to carbonyl is necessary for activity. Despite the lack of IC 50 values reports, AB0022A proved effectual against the three cell lines compared to Pf-1 [44] (Fig. 2).…”
Section: All the Polychlorinated Biphenyl (Pcb) Andmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, Pf-2 was found to lack any substantial cytotoxicity.Pf-1 and AB0022A exhibited the constraint of the tested cell lines (K562, HeLa and 3T3-L1), which indicates that a free phenolic group connected to carbonyl is necessary for activity. Despite the lack of IC 50 values reports, AB0022A proved effectual against the three cell lines compared to Pf-1 [44] (Fig. 2).…”
Section: All the Polychlorinated Biphenyl (Pcb) Andmentioning
confidence: 90%
“…1). Two dibenzofurans dubbed Pf-1 and Pf-2 were recently secluded from dictyostelium discoideum, another slime mold [43,44].…”
Section: All the Polychlorinated Biphenyl (Pcb) Andmentioning
confidence: 99%
“…These studies have now been extended to the characterization of curcumin and naringenin, which were found to inhibit development and/or growth (Cocorocchio et al, 2018;Swatson et al, 2017;Garige and Walters, 2015;Waheed et al, 2014). The polyketide Differentiation Inducing Factors (DIFs) 1-3, which are produced by Dictyostelium cells and induce stalk cell differentiation (Masento et al, 1988), and several of their synthetic derivatives have been shown to have not only anti-tumoral (Arioka et al, 2017;Dubois et al, 2016;Kubokura et al, 2015;Takahashi-Yanaga et al, 2014), but also anti-microbial activities, interestingly against Gram-positive, but not Gram-negative, bacteria (Kubohara et al, 2019), suggesting that Dictyostelium can be an important source in drug discovery (Kubohara and Kikuchi, 2018).…”
Section: Dictyostelium As a Model For Biomedical Research: Recent Conmentioning
confidence: 99%
“…There are, clearly, some limitations that make studies with lower organisms still unavoidable (Rine, 2014). Human disease phenotypes in many cases do not provide clues about the underlying molecular defect, thus unbiased genetic experiments in experimentally tractable organisms are required to establish Human disease or biomedical research Most recent reviews or relevant papers Microbial infections and host-pathogen interactions Cardenal-Muñoz et al, 2018;Swart et al, 2018;Steiner et al 2018;Koliwer-Brandl et al 2019;Brenz et al 2017 Mitochondrial diseases Chen et al 2017Chen et al , 2018Annesley et al 2014 Neuronal lipoid lipofuscinosis McLaren et al 2019;Smith et al, 2019 Poly-Q diseases Santarriaga et al 2018; Shwachman-Bodian-Diamond syndrome Weis et al, 2015 Pharmacogenetic research Wauters et al, 2019;Cocorocchio et al 2018;Kubohara and Kikuchi, 2018;Kubohara et al 2019;Arioka et al 2017;Dubois et al 2016…”
Section: Is There a Future For Dictyostelium As A Model Organism?mentioning
confidence: 99%
“…DIF-1 is one of the most well-characterized differentiationinducing molecules in Dictyostelium. There are many reviews concerning experiments of DIF-1, including some on various biomedical activities in mammalian cell lines (Williams, 2006;Kay and Thompson, 2009;Fukuzawa, 2011;Kubohara and Kikuchi, 2018). Therefore, here we focus on the biosynthetic pathway of DIF-1 and the function of DIF-1, which was revealed by the knockout mutants of biosynthetic enzyme genes (Fig.…”
Section: Dif-1: Biosynthesis and Inactivationmentioning
confidence: 99%